Pengaruh Gaya Kepemimpinan, Lingkungan Kerja Dan Budaya Organisasi Terhadap Kinerja Karyawan PT. Kala Group Semarang - Wulansari, Mayang; Suhana, Suhana (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to assess the inflluence of leadership styles, working enviroment and organizational culture on employee performance. The research was conducted at PT. Kala Group Semarang using food and beverage as samples. Convenience sampling is a method used to select samples. Data validity test using factor analysis. Data analysis is done using SPSS software version 27.0. The results showed that leadership styles has not have a significant impact on employee performance. Other findings, the work enviroment and organizational culture have a significant influence on employee performance. This research contributes both theoretically and practically.